O processo de referenciação em textos do blog do Folhateen - Soares, Flávia Aparecida (2012)
This descriptive and qualitative work aims to analyze texts reference processes in Folhateen blog, specifically the introduction, retaken and replacement of textual elements or referential expressions in order to verify if the strategies interfere on text progression and (re)elaboration of text meaning. Folhateen blog was chosen for its interactive nature and being responsible for publishing teenagers’ texts (between 13 and 19 years old) and so, containing teenagers’ ideas, points of views and values/the texts producers. In order to achieving the proposed target, the study was based on the Reference Theory of Araujo (2004), Cavalcante (2011, 2000), Koch (2009, 2008, 2005, 2004, 2001), Koch & Elias (2010, 2009), Marcuschi (2005a, 2005b), Mondada & Dubois (2003) among others. This study allowed the analyses of the introduction, retaken, expression and textual references replacement, what let us envision how these elements interfere/collaborate for textual progression, as well as, (re)elaboration of the texts meaning. It was also verified that the textual progression is only possible by the author’s capability of establishing a bridge between the initially defended thesis and the developed argument sequences in the text content. Once the corpus is composed of texts which language is peculiarly characteristic of adolescents we expect as public elementary school teachers that this research contributes for the hard task of educating readers and texts producers.